Fluorescence brightness and photostability of individual copper (I) oxide nanocubes. Issue 1 (December 2017) - Zohora, Nafisa; Kandjani, Ahmad; Orth, Antony; Brown, Hannah; Hutchinson, Mark; Gibson, Brant
Abstract Conventional organic fluorophores lose their ability to fluoresce after repeated exposure to excitation light due to photobleaching. Therefore, research into emerging bright and photostable nanomaterials has become of great interest for a range of applications such as bio-imaging and tracking. Among these emerging fluorophores, metal oxide-based nanomaterials have attracted significant attention as a potential multifunctional material with photocatalytic and angeogenisis abilities in addition to fluorescnce applications. However, most of these applications are highly dependent on size, morphology, and chemo-physical properties of individual particles. In this manuscript, we present a method to study the intrinsic optical characteristics of individual copper (I) oxide (Cu2 O) nanocubes. When excited at 520 nm using only 11 µW excitation power (1.7 W/cm2), individual nanocubes were observed to emit light with peak wavelengths ~760 nm which is conveniently within the near-infrared 1 (NIR1) biological window where tissue autofluorescence is minimal. Bright and photostable fluorescence was observed with intensities up to 487 K counts/s under constant illumination for at least 2 minutes with a brightness approximately four times higher than the autofluorescence from a fixed cumulus-oocyte complex. With near-IR emission, high fluorescence brightness, and outstanding photostability, Cu2 O nanocubes are attractive candidates for long-term fluorescent bioimaging applications.